ELEMENTS ANALYSIS OF INDICATORS FOR FIRMS IN NEW NETWORK BASED ECONOMY - Ioan I., GÂF-DEAC (Strategii Manageriale)
Network - as a comprehensive structure - can be considered "unconventional formula" and intercessory actions to reduce transaction costs between operators of composition. Elements of analytical indicators for the business at the new economy concerns: network company related new economy; potential network; internal resources of knowledge; networked learning facilities; external sources of knowledge; network relationships; new intellectual capital; complementarities of knowledge; network global indicators and indicators for corporate networking. In this context, the aim is conceptual preoccupations for commitment guarantee for the establishment in the scientific, economic and managerial Romania's competitive advantage in absolute terms compared to relativity concerns only obtain comparative advantages.